PENGARUH KONFORMITAS TEMAN SEBAYA TERHADAP PERILAKU KONSUMTIF PADA SISWA SMA DI KOTA BANDAR LAMPUNG - Dyanti Mahrunnisya; Mintasih Indriayu; Dewi Kusuma i Wardani (JURNAL ELASTISITAS: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2022)
This study aims to determine the effect of peer conformity on consumptive behavior in students in the city of Bandar Lampung. The method used in this research is descriptive verification method with ex post facto and survey approaches. Data collection techniques were carried out using a questionnaire. The population in this study were all students of class XI IPS of Senior High School in Bandar Lampung, which consisted of 17 schools. The sample in this study was taken by dividing 17 schools based on the ranking strata namely high, medium, low, based on the value of passing grade to enter the school, then selected three schools randomly to represent each rank. Then the researchers had a population of 414 people. The sampling technique in this study was Proportional Stratified Random Sampling, with a total sample of 165 students. The questionnaire used in this study uses a Likert scale, which is a measurement scale used to measure people's attitudes, opinions, and perceptions about social phenomena. The results showed the influence of peer conformity on consumptive behavior by 32.4%. Conformity is one factor a person becomes consumptive, the higher a person's conformity, the higher the consumptive behavior.